Adaptation of the internet business self-efficacy scale for Peruvian students with a commercial profile - Torres-Miranda, Julio Samuel; Ccama, Celinda Aroni; Niño Valiente, Juana Rosa; Turpo-Chaparro, Josué Edison; Castillo-Blanco, Ronald; Mamani-Benito, Oscar (Frontiers in Education, 2024)
Introduction Given the lack of instruments to evaluate the sense of efficacy regarding entrepreneurial capacity in Peruvian university students, this study aims to translate into Spanish, adapt, and validate the Internet Entrepreneurial Self-efficacy Scale in Peruvian university students with a commercial profile. Method An instrumental study was conducted where 743 students between 18 and 42 years old participated in careers with a commercial profile (Administration, Accounting, Economics, and other related careers) from the three regions of Peru (Coast, Mountains, Jungle). For analyzing content-based validity, Aiken’s V coefficient was used, Cronbach’s Alpha coefficient was used for reliability, and internal structure was used through confirmatory factor analysis. Results A reverse translation was achieved in the appropriate time and context. All items proved to be valid (V >0.70), and the reliability of the instrument was very good (α = 0.96). Concerning the results of the confirmatory factor analysis, the three-dimensional structure of the instrument was evaluated, finding an adequate fit [χ2(87) = 279.6, p < 0.001, CFI = 0.972, RMSEA = 0.049, SRMR = 0.025], based on this, the original internal structure was corroborated. In complementary analyses, it was found that the instrument is invariant according to sex and university. Finally, it demonstrates significant correlations with scales that measure similar constructs. Conclusion The Entrepreneurial Self-efficacy Scale on the Internet shows adequate psychometric properties; therefore, it can be used as a management tool to analyze the entrepreneurial capacity of university students with a commercial profile. These findings allow universities to evaluate the entrepreneurial capabilities of students who can promote sustainable businesses, which in turn improves the relationship between the University, state, and company.